The Changing Incidence of Malaria in Indonesia: A 9-Year Analysis of Surveillance Data - Dewi Nur Aisyah; Desrina Sitompul; Haniena Diva; Siti Nadia Tirmizi; Lukman Hakim; Asik Surya; Riskha Tiara Puspadewi; Helen Dewi Prameswari; Wiku Adisasmito; Logan Manikam (Advances in Public Health)
Conclusions: Progress has been made in province-level malaria elimination, especially outside Papua and West Papua. To prevent the persistence of endemic malaria pockets in Papua and West Papua, there is a need for greater coordination of and further dedication of financial resources toward efforts to eliminate malaria in these provinces. These efforts should be supported by an improvement in surveillance capacity, the inclusion of information on the parasite species responsible for malaria cases in routine surveillance initiatives, and the use of culturally tailored interventions to maximize health-seeking behaviors and intervention uptake.